EARLY CHILDHOOD, LANGUAGE DEVELOPMENT AND ITS ACQUISITION - Isaac, Nungala Usman (Fakultas Agama Islam Universitas Islam As Syafi'iyah, 2024)
Early childhood language development and acquisition is a critical period of rapid growth, laying the foundation for future cognitive, social, and emotional success. This review synthesizes empirical research on language acquisition in children from birth to age 5, examining stages, theories, and influencing factors. Evidence-based strategies for supporting language development are highlighted, including parent-child interaction, language-rich environments, and educational programs. Implications for parenting, education, and research are discussed, emphasizing interdisciplinary collaboration and evidence-based practices to foster optimal language development. Early childhood education lays the cornerstone for language development, a critical aspect of cognitive, social, and emotional growth. This study examines the pivotal role of early childhood education in shaping language skills in children aged 2-6 years. A comprehensive review of existing literature highlights the interplay between teacher-child interactions, play-based learning, and language-rich environments in fostering phonological awareness, vocabulary expansion, and syntactic development. The impact of storytelling, reading aloud, and dialogic reading on language acquisition is also explored. Furthermore, this research investigates the effects of socioeconomic status, bilingualism, and technology integration on language development in early childhood settings. The findings underscore the significance of evidence-based instructional strategies, parental involvement, and tailored interventions to support diverse language learners. The study's implications inform educators, policymakers, and parents on effective practices to promote language development and foundation literacy skills in young children.